Altered brain activities in mesocorticolimbic pathway in primary dysmenorrhea patients of long-term menstrual pain - Liu, Ni; Li, Yingqiu; Hong, Yueying; Huo, Jianwei; Chang, Tai; Wang, Haoyuan; Huang, Yiran; Li, Wenxun; Zhang, Yanan (Frontiers in Neuroscience, 2023)
Background: Primary dysmenorrhea (PDM) is often associated with emotional abnormalities, central sensitization and occurrence of many other chronic pain conditions in later life. Herein, the study probed into altered intraregional and interregional brain spontaneous activity in PDM patients and expounded possible neurobiological mechanisms through resting-state functional magnetic resonance imaging (rs-fMRI). Methods: Thirty-three PDM patients and thirty-six demographic-matched healthy controls (HCs) were recruited and underwent resting state functional magnetic resonance imaging(rs-fMRI) scan during menstruation. Regional homogeneity (ReHo) and mean amplitude of low-frequency fluctuations(mALFF) analysis was applied to compare the difference of intraregional brain spontaneous activity between the two groups, then the regions showed ReHo and mALFF group difference were used as seed for seed-based functional connectivity (FC) analysis to explore the difference of interregional functional activity. Pearson correlation analysis was conducted between rs-fMRI data and clinical symptoms in PDM patients. Results: Compared to the HCs, PDM patients had significantly higher ReHo values in the right hippocampus (Hip), temporal polar superior temporal gyrus, nucleus accumbens (NAc) and pregenual anterior cingulate cortex (ACC); and lower ReHo values in the left Cerebellum_8, middle temporal gyrus (MTG), inferior temporal gyrus (ITG), rolandic operculum. And PDM patients had significantly increased mALFF values in the left ITG; and decreased mALFF values in the left postcentral gyrus (PoCG) and middle frontal gyrus (MFG). Compared to the HCs, PDM patients showed enhanced FC between the right Hip and the left precentral gyrus (PrCG), the right NAcc and the left supraorbital frontal gyrus and the right PrCG, the right temporal polar superior temporal gyrus and the left PrCG, the left MFG and the right superior frontal gyrus (SFG), and weakened FC between the left rolandic operculum and bilateral PoCG. The anxiety symptoms are positively correlated with increased ReHo values of the right temporal polar superior temporal gyrus and negatively correlated with FC values between the left MFG and the right SFG. Conclusion: Our results indicate altered intraregional brain activity and interregional FC in regions centered on mesocorticolimbic pathway, sensorimotor brain regions and temporal lobe in PDM patients during menstruation, providing more evidence for the neurobiological changes of PDM.